The Impact of Business Intelligence on Business Intelligence Execution Capacity in Strategic Management: The Mediating Role of Digital Literacy - Mehmet Özgen; Rana Özyurt Kaptanoğlu (Proceedings, 2024)
Strategic management involves addressing irregularities, pursuing objectives, and selecting optimal actions in an economic context [...]